Youth Organizations as Catalysts for Conflict Resolution: Insights from the Historical Legacy of the Youth Pledge - Yohanes Nainggolan; Pujo Widodo; Djayeng Tirto Soedarmono; Anang Puji Utama; Badia Ni Partahi Nainggolan (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
In the contemporary global context, societies increasingly face complex social conflicts driven by identity politics, ideological polarization, and socio-economic disparities. Youth organizations have emerged as important actors in promoting social cohesion, dialogue, and conflict resolution. This study examines the role of youth organizations as catalysts for conflict resolution by drawing insights from the historical legacy of the Youth Pledge (Sumpah Pemuda) of 1928. The research aims to analyze how youth-led collaboration contributed to national unity and how the values embedded in the Youth Pledge remain relevant for addressing contemporary social conflicts. This study employs a Systematic Literature Review (SLR) combined with a simplified qualitative meta-analytic synthesis to examine scholarly literature related to youth movements, conflict resolution, and peacebuilding. The literature was collected from major academic databases such as Google Scholar, Scopus-indexed journals, and Web of Science, focusing primarily on studies published within the last five years. The findings indicate that youth organizations historically played a critical role in fostering unity through cross-regional collaboration and collective identity formation, which culminated in the declaration of the Youth Pledge. The study also identifies key values (unity in diversity, collective identity, national solidarity, and collaborative leadership) as relevant frameworks for modern conflict resolution. In contemporary contexts, youth organizations contribute to peacebuilding through community dialogue, tolerance campaigns, and grassroots mobilization for social harmony.